Investigating the Role of Stress-Preventive Leadership in the Workplace Hospital: The Cross-Sectional Determination of Relational Quality by Transformational Leadership - Stuber, Felicitas; Seifried-Dübon, Tanja; Rieger, Monika A.; , Contributors of the SEEGEN Consortium; Zipfel, Stephan; Gündel, Harald; Junne, Florian; Rothermund, Eva; Mulfinger, Nadine; Jarczok, Mark; Angerer, Peter; Maatouk, Imad; et al. (Frontiers in Psychiatry, 2019)
Introduction: A good relationship quality between leaders and subordinates promotes mental health and prevents stress in hospital subordinates. Therefore, it is important to identify specific behavioral characteristics which determine the quality of working relationships at this workplace. This study will identify specific leadership characteristics which support the development of a positive relationship between hospital leaders and subordinates. Methods: A cross-sectional study design was applied. A total number of 1137 leaders and subordinates working at a tertiary hospital in Germany assessed transformational leadership style as a subordinate oriented leadership style and leader–member relationship quality by self-reporting questionnaires (integrative leadership questionnaire FIF, leader-member exchange questionnaire LMX-7). The data were statistically analyzed by mean comparisons and multiple linear regression analysis. Results: Leaders rated their own transformational leadership style (M = 3.98, SD = 0.43) systematically higher than subordinates assessed their leaders (M = 2.86, SD = 1.04). Evaluation of relationship quality showed similar results: leaders evaluated their relationship quality to one exemplary subordinate higher (M = 4.06, SD = 0.41) than subordinates rated their relationship quality to their direct leader (M = 3.15, SD = 0.97). From the subordinates’ perspective the following sub-dimensions of transformational leadership ‘individuality focus’, ‘being a role model’, ‘fostering innovations’ and ‘providing a vision’ showed large effect sizes in the regression analysis of relationship quality (R2 = 0.79, F (6,698) = 438.27, p <.001, f2= 1.94). Discussion: The exploration of potential determinates of relationship quality at the workplace hospital can for example support the development of leadership training programs with a focus on transformational leadership style. This might be an opportunity to foster high relationship quality between leaders and subordinates and consequently might present one strategy to prevent stress in the health care sector.